The cancer stem cell paradigm: a new understanding of tumor development and treatment - Johnathan Ebben; Daniel M. Treisman; Michael Zorniak; Raman G. Kutty; Paul A. Clark; John S. Kuo (2010)
Importance of the field: Cancer is the second leading cause of death in the United States, and therefore remains a central focus of modern medical research. Accumulating evidence supports a 'cancer stem cell' (CSC) model – where cancer growth and/or recurrence is driven by a small subset of tumor cells that exhibit properties similar to stem cells. This model may provide a conceptual framework for developing more effective cancer therapies that target cells propelling cancer growth.